2023
DOI: 10.1101/2023.01.29.526146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charge-State-Dependent Collision-Induced Dissociation Behaviors of RNA Oligonucleotides via High-Resolution Mass Spectrometry

Abstract: Mass spectrometry (MS)-based analysis of RNA oligonucleotides (oligos) plays an increasingly important role in the development of RNA therapeutics and in epitranscriptomic studies. However, MS fragmentation behaviors of RNA oligos are understood insufficiently. In this study, we characterized the negative-ion-mode fragmentation behaviors of 26 synthetic RNA oligos of four to eight nucleotides (nt) in length by collision-induced dissociation (CID) using a high-resolution, accurate-mass instrument. We find that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…For RNA oligos with one or two terminal phosphate groups, the precursors with the loss of phosphoric acid or metaphosphoric acid anion were also calculated and matched with the observed peaks. Cyanate anion (NCO - ) loss was not included here since the terminal pyrimidine bases were not contained in all oligos we used 15,30 . The observed monoisotopic peak was assigned to a theoretical ion within a mass tolerance of 10 ppm.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For RNA oligos with one or two terminal phosphate groups, the precursors with the loss of phosphoric acid or metaphosphoric acid anion were also calculated and matched with the observed peaks. Cyanate anion (NCO - ) loss was not included here since the terminal pyrimidine bases were not contained in all oligos we used 15,30 . The observed monoisotopic peak was assigned to a theoretical ion within a mass tolerance of 10 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Collectively, after CIP treatment, all terminal phosphate groups had been eliminated, and the CID fragmentation behaviors of RNA oligos with both terminal hydroxyl groups we reported in ref. 15 has also indicated that this sample treatment could improve MS analysis for RNA sequencing and PTxM characterization using tandem mass spectrometry. Therefore, we highly recommend CIP treatment prior to MS analysis when the digested products from RNA samples contain either one or two terminal phosphate groups.…”
Section: Cip Treatment Can Effectively Remove Terminal Phosphate Grou...mentioning
confidence: 99%
See 3 more Smart Citations